Applying Location Quotient and Shift-Share Analysis in Determining Leading Sectors in Teluk Bintuni Regency - Maspaitella, Marcus; Parinussa, Sisilia M.; Ketysia Imelda tewernusa (Journal of Developing Economies, 2021)
Economic growth is an important aspect that reflects the success of a country or region's economic development. The changes of its driving sectors mainly influence the changes in economic growth. This study aims to identify the leading economic sectors and analyze the sectoral shifts of the Teluk Bintuni regency's economy. The data used in this study is the Gross Regional Domestic Product of both Teluk Bintuni Regency and Papua Barat province in the period from 2010 to 2018. In determining the leading sectors and analyzing the sector using Location Quotient and Shift-Share analysis. The results suggested that the manufacturing and mining, and quarrying sectors were the base sectors of Teluk Bintuni's economy. However, the result of Shift-Share analysis highlighted construction, education services, procurement of electricity and gas, and public administration, defense, and compulsory social security as competitive and progressive sectors during the same period. Policy implications of this study include evaluating and reformulating development strategies and programs and considering sectoral interconnection for further development planning. Keywords: Location Quotient, Shift-Share, Leading Sectors, Teluk Bintuni JEL: O11; R11; R58